The Effect of Growth and Systematic Risk on the Firm’s Value: Profitability as a Mediating Variable - Mulyanto Nugroho; Abdul Halik (Universitas Hayam Wuruk Perbanas, 2020)
This research aimed to examine the impact of growth and systematic risk on company value, mediated by profitability in insurance companies listed on the Indonesia Stock Exchange (IDX). There are 88 companies in the financial sector in the insurance sub-sector listed on the IDX. They were taken as the population by using the purposive sampling technique. The sample of this study consisted of fourteen insurance companies. The data is analyzed using partial least square structural equation modeling (PLS-SEM). It was found that growth has a significant positive effect on profitability, and profitability has a significant positive effect on firm value. It means that profitability fully mediates the effect of growth on firm value. On the contrary, growth does not have a significant direct effect on firm value. Systematic risk has no significant effect on profitability and firm value. These findings are expected to have a good impact on investors and firms’ managers in Indonesia by looking at the growth and its impact on current corporate values.